2016
DOI: 10.1088/0953-4075/49/18/185601
|View full text |Cite
|
Sign up to set email alerts
|

Atomic RABBITT-like experiments framed as diatomic molecules

Abstract: The single ionization of noble gas atoms by an attosecond pulse train assisted by an infrared laser field is theoretically investigated by means of a non-perturbative model that under certain approximations gives closed-form expressions for the angular distributions of photoelectrons. A very good agreement between our predictions and experiments is observed. Interestingly, our model allow us to interpret these angular distributions as two-center interferences where the separation between centers is governed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…For completeness we note that the present semiclassical description of the interhalf-cycle interference factor allows also for an alternative intuitive interpretation following Ref. [23].…”
Section: Izationmentioning
confidence: 77%
See 1 more Smart Citation
“…For completeness we note that the present semiclassical description of the interhalf-cycle interference factor allows also for an alternative intuitive interpretation following Ref. [23].…”
Section: Izationmentioning
confidence: 77%
“…The relative phase between these two ionization paths permits the interferometric extraction of phase shifts and time delays from the asymptotic behavior of the scattered electron wave packet. Accurate phase and time information can be directly extracted from numerically exact solutions of the time-dependent Schrödinger equation (TDSE) [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The SFA is regularly used in description of the sidebands of the main photoelectron line in XUV + IR ionization by atto-and femtosecond pulses (Kazansky et al, 2010(Kazansky et al, , 2011Jiménez Galán et al, 2013;Picard et al, 2004). It allows significant advances in developing analytical derivations, in particular, closed-form expressions for the angular distributions of photoelectrons in two-colour XUV + IR ionization were obtained (Boll and Fojón, 2016).…”
Section: Strong-field-type Approximationsmentioning
confidence: 99%
“…(2)) takes into account the Coulomb interaction of the electron with the residual target in the final channel of the reaction. It was shown that this interaction must be accounted for to describe the photoionization reaction with neutral targets in a realistic way [1, 13,14].…”
Section: Theory I Coulomb Continuum (Cc) Modelmentioning
confidence: 99%